DEVELOPMENT AND VALIDATION OF LIQUID CHROMATOGRAPHY COUPLED WITH TANDEM MASS SPECTROMETRY METHOD FOR ESTIMATION OF LENVATINIB IN HUMAN PLASMA - I, Srikanth; A, Prameela Rani (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective:Â This study was to develop and validate a liquid chromatographyâ€“tandem mass spectrometry (LCâ€“MS/MS) for the quantification of lenvatinib (LT) in human plasma. Methods: A simple, sensitive and specific LCâ€“MS/MS method was developed for quantification of LT in human plasma using LTD4 as internal standard (IS). The analytical method consists of liquidâ€“liquid extraction of plasma sample followed by the determination of LT by a LCâ€“MS/MS. The analyte was separated on a Zorbax Eclipse XDB-C18 (150Ã—4.6 mm, 5 Î¼) column with an isocratic mobile phase of acetontrile:0.1% formic acid (80:20 v/v) at a flow rate of 0.6 mL/minutes. The protonated ions were formed by a turbolon spray in a positive mode were used to detect analyte and IS. The MS/MS detection was made by monitoring the fragmentation of m/z 427.10â†’370.10 for LT and m/z 430.30â†’370.10 for IS on a MS. Result: The method was validated with the correlation coefficients of (r2) â‰¥0.995 over a linear concentration range of 10.20-501.60 pg/mL. This method demonstrated intra- and inter-day precision within 1.06-2.42% and 0.03-0.55% and accuracy within 95.64-100.08% and 97.16-100.07%. Conclusion: This method is suitable and convenient to pharmacokinetics and bioavailability studies for estimation of LT in biological samples by LCâ€“MS/MS.